Kajian Potensi Kulit Buah Mangga Sebagai Bahan Pangan - Mas’ud, Fajriyati (Jurnal Agritechno, 2023)
Mango peel is a by-product of fruit processing which can pollute the environment. In this study, a proximate analysis was carried out which included water content, carbohydrates, protein, fat, minerals, and several bioactive compounds of mango peel, the study was conducted on the potential for its utilization as a food ingredient. The water content of mango peel is 66% -70%, carbohydrates are more than 70%, protein and fat are around 2 - 3 g/100g respectively, fiber content is around 30 - 38 g/100g, total phenolic compounds are 80 - 90mg/g, and carotenoids 2 - 4 mg/g. One way that can be done to utilize mango peel is to modify it into a powder form by washing and blanching, drying and milling. In the form of flour, various benefits of mango peel can be obtained, especially in the development of functional food.